Household Chaos and Parenting Competence Are Associated with Low-Income Mothers' Use of Food to Soothe: A Longitudinal Analysis in Early Infancy. (29th May 2020) - Ruggiero, Cara; Harris, Holly; Bailey-Davis, Lisa; Savage, Jennifer
Abstract: Objectives: Use of food to soothe (FTS) infant distress has been linked to later obesity risk. Infant characteristics influence mothers' use of FTS, but less is known about how broader family characteristics, like parenting or the home environment impact FTS. We aimed to examine whether maternal parenting competence and household chaos, factors known to influence responsive parenting, were associated with the use of FTS over time. Methods: This secondary analysis includes 288 low-income mothers and their full-term newborns participating in the WEE Baby Care study. The Babies Basic Needs Questionnaire was used to assess emotional FTS (e.g., in response to infant distress, maternal stress) and contextual FTS (e.g., car, church) at infant ages 2, 5, and 7 months. The Confusion, Hubbub and Order Scale (chaos) and the Parenting Sense of Competence Scale (total competence, parenting satisfaction, parenting self-efficacy) were completed at 2 months. Mixed linear models adjusted for study group were used to examine emotional and contextual FTS over time. Results: The use of FTS decreased over time from 2 to 7 months of age ( P < 0.05). Mean (SD) chaos was 25.7 (5.3) with a possible range from 15 to 60. Mean (SD) competence was 78.8 (9.8) with a possible range of 16 to 96. Lower competence and parenting satisfaction (both P < 0.0001) and higher chaos ( P = 0.03) were associated with mothers' greater use of emotional FTS. Competence ( P = 0.46) and chaos ( P = 0.29) were not associated with mothers' use of contextual FTS. Lower parenting satisfaction was marginally associated with mothers' greater use of contextual FTS ( P = 0.06). Parenting self-efficacy was not associated with the use of FTS. Conclusions: Results suggest that maternal parenting characteristics and household chaos may be potentially modifiable factors related to mothers' use of FTS, especially to relieve their personal or their infants' emotional distress. Interventions that target low-income mothers' feeding practices may need to address a broad range of maternal and household characteristics. Funding Sources: Health Resources and Services Administration of the U.S. Department of Health and Human Services, Maternal and Child Health Field-initiated Innovative Research Studies Program.